PARTICIPATORY DIAGNOSIS OF HYPERTENSIVE PATIENTS IN THE FAMILY HEALTH STRATEGY: EXPERIENCE REPORT IN THE TERRITORY OF EUNÁPOLIS, BRAZIL - Almeida da Silva, Flaelma; Rocha Brito, Flávia; de Lima, Diana; Vitoriano Leonel, Ariel; Jéssica Gomes Belém, Cícera; Galdino Neto, Francisco; Ismyrlly de Lavor, Hemylly; Victor dos Santos de Deus, João; Pereira Santos, Livia; Maria Ferreira Moreira da Silva, Sofia (Health and Society, 2025)
This article presents an experience report derived from a university outreach project linked to the Medical School of Faculdade Pitágoras de Eunápolis, aiming to strengthen primary health care through the analysis of the profile of hypertensive patients enrolled in the Moisés Reis Basic Health Unit, located in the municipality of Eunápolis, Bahia, Brazil. The initiative involved territorial mapping of a micro-area, home visits, educational dialogue, and the application of a semi-structured questionnaire addressing lifestyle habits, clinical aspects, and treatment adherence. The methodology adopted was quantitative-descriptive, without any interventional or invasive procedures, in full respect of ethical principles and local health realities. The findings revealed a predominance of women over 50 years of age, high adherence to antihypertensive medication, regular engagement in leisure activities, and low incidence of smoking and alcohol consumption. However, many participants presented altered blood pressure levels and symptoms associated with hypertension. The experience highlighted the positive impact of educational actions and active listening on users’ awareness of their own health conditions. The project reinforces the transformative role of university outreach in medical education by integrating scientific knowledge with social commitment and generating relevant data for public health planning.